Prevalence of sleep-disordered breathing and associations with orofacial symptoms among Saudi primary school children - Laila Baidas; Asma Al-Jobair; Huda Al-Kawari; Aram AlShehri; Sarah Al-Madani; Hana Al-Balbeesi (BMC, 2019)
Abstract Background This study aimed to determine the prevalence of sleep-disordered breathing among primary school children in Riyadh, Saudi Arabia, and to evaluate associations between sleep-disordered breathing and respiratory conditions/orofacial symptoms. Methods In this cross-sectional study, 1600 questionnaires were distributed to Saudi boys and girls aged 6-12 years from 16 primary schools in Riyadh. The questionnaire covered relevant demographic and personal characteristics, presence of respiratory conditions and orofacial symptoms, and the Pediatric Sleep Questionnaire. The latter was used to assess the prevalence of symptoms of sleep-disordered breathing and was completed by the participating children's parents. Results In total, 1350 completed questionnaires were returned (85% response rate). The children' mean age was 9.2 ± 1.8 years; 733 (54.3%) were boys and 617 (45.7%) girls. Overall, 21% of children were at high risk of sleep-disordered breathing. The prevalence of snoring was 14.4% and that of sleep apnea 3.4%. Boys were at higher risk of sleep-disordered breathing than girls (P = 0.040). Children with respiratory conditions or orofacial symptoms were at higher risk of sleep-disordered breathing (P < 0.0001) than children without these conditions/symptoms. Conclusions Around 21% of Saudi children are at risk of sleep-disordered breathing. There is a strong association between sleep-disordered breathing symptoms and the presence of respiratory conditions or orofacial symptoms.